THE REUSE OF ARABIC-MALAY SCRIPT IN RIAU PUBLIC SPHERES - Yendra; Emil Septia; Suci Maiza (LLDIKTI Wilayah X, 2023)
The Arabic-Malay script was a writing system used by the Malay society in the Indonesia archipelago starting from the 13th century. Since the arrival of European colonization in the 17th century until the 20th century, the Arabic-Malay script began to be abandoned because colonialism introduced a new education system that required the use of Latin script. Recently, the phenomenon of reusing Arabic-Malay script has become widespread in Riau, especially in public spheres. This research discusses the reuse of Arabic-Malay script in Riau public spheres from Linguistic Landscape (LL) perspective which refers to the concept of public signs and personal signs. This research was designed using qualitative descriptive methods. The research procedures carried out include an empirical survey of language signs in public sphere, classification of language signs, and analysis of motives for reusing Arabic-Malay script in public spheres. The results of this research conclude: first, the language used in public sign which written in Arabic-Malay script is Bahasa Indonesia; second, the classification type of signs in LL is public sign which is top-down by the local government; and third, the motive for reusing Arabic-Malay script is to reshape the Malay ethnic space in Riau's public space. In other words, the preference of Arabic-Malay script used on public signs shows that the identity of the place is indeed a symbolic marker of Malay ethnicity.